The proficiency Level of Female Primary School Pupils in Reading Comprehension Skills from the Viewpoint of their Teachers - AL-Rashidi, Meaad Mansor; Haji, Khadijah Mohammed (Journal of Educational and Psychological Sciences, 2021)
The current research aims to identify the level of proficiency of upper-grade female primary school pupils in the elementary stage in reading comprehension skills from the viewpoint of their teachers, to detect the teachers, viewpoints about their pupils, level of proficiency in reading comprehension skills that are due to the difference in the grade, and to identify a list of reading comprehension skills that are necessary for upper grade’s students. The author used the descriptive survey method and applied the research tool (questionnaire) on a sample of (261) teachers out of (815) at a percentage of (32%), having verified their validity and reliability. She also used a set of statistical methods including: Alpha Cronbach, Pearson Correlation Coefficient, repetitions, percentages, arithmetic means, standard deviations, single analysis of variance (ANOVA) test, and Scheffe post hoc difference test. The author found that that the proficiency level of female primary school pupils in those skills is great in general as well as in the skills of direct, deductive, and creative comprehension, while it was moderate in the skills of appreciation and critical understanding. There are statistically significant differences at the level of (0.05) in direct comprehension skills due to the teaching grade variable, as it came in favor of the fourth and fifth grades. There are no statistically significant differences in the rest of the skills. Finally, in light of the research findings, a set of recommendations were made.